Learning Architecture: How U-Shaped Desks Affect Classroom Dynamics - Senad Orhani (Yayasan Al Hidayah, 2025)
U-shaped desk organization on classroom dynamics, focusing on teachers’ experiences and perceptions. The U-shape is considered one of the most effective student seating patterns, as it allows for increased visual contact, fostering collaboration and active involvement in the learning process. Through a qualitative methodology, the research will be based on semi-structured interviews and direct classroom observations, collecting data from teachers at different levels of education. The analysis will focus on how this form of seating affects interaction, discipline, motivation, and the building of a collaborative classroom climate. The results showed that the U-shape desk arrangement significantly improves student interaction, engagement, and discipline, creating a more collaborative and democratic classroom climate, although practical challenges such as limited space remain an obstacle to its full implementation.